Shocks, changes in outreach and lending technologies in microfinance: The Bolivian experience - Jorge G. M. Leitón Quiroga (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2006)
The Bolivian evidence shows that microfinance lending technologies are well designed to cope with different kinds of risk. The innovations provided in this financial sector show more strengths than weaknesses to overcome information asymmetries. Furthermore, group and individual loans are providing good mechanisms to cope with idiosyncratic and systemic shocks. Certainly, different microfinance technologies developed in Bolivia have shown good performance in terms of outreach and sustainability. – – La experiencia de las microfinanzas en Bolivia muestra que las tecnologías de crédito tienen un buen dise\~no para enfrentar diferentes tipos de riesgo. Las innovaciones realizadas en este sector financiero muestran más fortalezas que debilidades para superar los problemas de información asimétrica. De esta manera, tanto los créditos grupales como individuales proveen de buenos mecanismos para enfrentar los riesgos idiosincrásicos y sistémicos. Las tecnologías microfinancieras desarrolladas en Bolivia han demostrado un buen desempe\~no en términos de outreach y sostenibilidad.
Keywords: G29; D81; 330; Microfinance; Information Asymmetries; Lending Technologies; Bolivia; Asymmetrische Information; Kreditgeschäft; Bolivien; Mikrofinanzierung